Upaya Pengenalan Umbi Porang dan Olahannya Sebagai Alternatif Makanan Tinggi Serat - Ratih Kusuma Wardani; Djamilah Arifiyana; Vika Ayu Devianti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Diabetes mellitus is a degenerative disease indicated by increased blood sugar levels. This disease can be prevented by adopting a healthy lifestyle, one of which is by consuming foods high in fiber and having a low glycemic index. Porang tubers are a high-fiber food with a low glycemic index. However, porang tubers cannot be consumed directly because of the high content of calcium oxalate, so it is advisable to consume porang tubers in processed forms such as porang rice, shirataki, porang pudding. This activity aims to provide information to the public about the benefits of porang tubers and their preparations for health, especially for someone with diabetes mellitus